Fa’āliyyah Ta’līm Mahārah al-Istimā’ bi Istikhdām Android li al-Jawwāl - Siti Jubaidah; Luluk Humairo Pimada; Penny Respaty Yurisa; Wildana Wargadinata (LISANIA: Journal of Arabic Education and Literature, 2020)
This study aims to develop the learning of Arabic listening skill by using technology especially Android media which is currently in great demand by millennial generation, and to find out how effective it is. To measure the effectiveness of learning Arabic listening by using Android, this study uses an experimental-based research applied to 32 tenth graders of Natural Science (IPA) at Islamic High School (Madrasah Aliyah/MA) Nasruddin Dampit. The data collection techniques used in this study are tests, namely pre-test and post-test and distributing questionnaires. The data analysis uses the t test formula. And based on the results of research that has been done, the results obtained t count = 5.21 and t table = 2.04 with a significant level α = 0.05. Thus t arithmetic t table = 5.21 2.04 which means the learning of Arabic listening by using android in MA Nasruddin is effective.